2020
DOI: 10.1002/anie.202011956
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Surface Oxidation of Cu Nanowires Improves Their Catalytic Selectivity and Stability toward C2+ Products in CO2 Reduction

Abstract: Copper nanostructures are promising catalysts for the electrochemical reduction of CO 2 because of their unique ability to produce alarge proportion of multi-carbon products. Despite great progress,t he selectivity and stability of such catalysts still need to be substantially improved. Here,w e demonstrate that controlling the surface oxidation of Cu nanowires (CuNWs) can greatly improve their C 2+ selectivity and stability.S pecifically,w ea chieve af aradaic efficiency as high as 57.7 and 52.0 %f or ethylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
121
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(122 citation statements)
references
References 45 publications
1
121
0
Order By: Relevance
“…Similarly, the coarsen of the dendritic Cu nanostructures in the course of CO 2 RR resulted in the loss of high index facets, which was believed to be responsible for the degradation of catalytic performance [13a, 14a] . A recent study demonstrated that a thicker and smoother Cu x O protective layer obtained by controlled surface oxidation could inhibit the disintegration of Cu nanowires and improve its catalytic stability to more than 22 h [15b] . In this study, it was demonstrated that abundant active sites that were induced under CO 2 RR conditions were well‐retained even after 240 h of electrocatalysis, which may be due to the thermodynamical stability of these active sites under CO 2 RR conditions [16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the coarsen of the dendritic Cu nanostructures in the course of CO 2 RR resulted in the loss of high index facets, which was believed to be responsible for the degradation of catalytic performance [13a, 14a] . A recent study demonstrated that a thicker and smoother Cu x O protective layer obtained by controlled surface oxidation could inhibit the disintegration of Cu nanowires and improve its catalytic stability to more than 22 h [15b] . In this study, it was demonstrated that abundant active sites that were induced under CO 2 RR conditions were well‐retained even after 240 h of electrocatalysis, which may be due to the thermodynamical stability of these active sites under CO 2 RR conditions [16] .…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the disintegration of structure and the loss of active sites,g raphene oxide wrapped and thick CuO x outer layer protected Cu nanowires showed enhanced stability for both structure and catalytic performance. [15] Recently,aCu nanowire catalyst was reported to maintain ah igh selectivity toward C 2 H 4 for over 200 hours of electrocatalysis,p ointing out the importance of stable stepped sites that formed through in situ during electrochemical activation. [16] Therefore,i ti so fg reat importance to maintain the stability of catalyst structure and active sites for improving the catalytic performance of Cu-based CO 2 RR electrocatalysts.O nt he other hand, although the conclusion is still pending, the crucial role of oxidized Cu species for the improvement of C 2+ production has been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the reduction process with two‐electron transfer, in which generating CO and formate, is economically viable according to the techno‐economic analysis [5] . Numerous efforts are thus focused on designing efficient electrocatalysts for CO 2 ‐to‐CO reduction with high Faradaic efficiency (FE) and high activity (such as CO partial current density) [6–9] . To date, carbon‐based materials, [6] noble metals (such as Ag), [7] metal oxides (CuO x and ZnO) [8,9] and metal chalcogenides (CdS and MoSe x ) [10–14] have been developed for electrochemically producing CO.…”
Section: Figurementioning
confidence: 99%
“…Numerous efforts are thus focused on designing efficient electrocatalysts for CO 2 ‐to‐CO reduction with high Faradaic efficiency (FE) and high activity (such as CO partial current density) [6–9] . To date, carbon‐based materials, [6] noble metals (such as Ag), [7] metal oxides (CuO x and ZnO) [8,9] and metal chalcogenides (CdS and MoSe x ) [10–14] have been developed for electrochemically producing CO. Among them, the stable nanorod‐like CdS electrocatalyst shows excellent CO FE of >95 % in aqueous solution by suppressing the competing hydrogen evolution reaction [12–14] .…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] On the other hand, carbon dioxide (CO 2 ) generated from industries and transportation is the principal greenhouse gas causing serious environmental concerns. [4][5][6][7][8] Thus, converting N 2 and CO 2 into value-added fuels and chemical products via the C-N coupling reaction is a promising approach for not only mitigating environmental issues and energy crisis but also high-value utilization of N 2 and CO 2 . [9][10][11][12] However, the highly stable double-bond (C]O, 806 kJ mol À1 ) in CO 2 molecules and the triple-bond (N^N, 940.95 kJ mol À1 ) in N 2 molecules make the inert gas molecules difficult to activate mildly.…”
Section: Introductionmentioning
confidence: 99%